2015
DOI: 10.1080/14606925.2015.1059608
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Ecology of Design Praxis

Abstract: The notion of ecological design has rightly been around for decades, yet a genuine praxis of designing ecologically has been slow to emerge. We believe this is a problem about how we understand our perception of and relationship with the other, the rest of nature and ourselves. This paper attempts to synthesize a new epistemology of design which we refer to as an ecology of design and in which we try to understand the systemic relationships which constitute the human ecology of living and in which the practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Designing living systems is an interconnected interaction of continuously evolving and self-organizing interventions for long-term vision of sustainable future. (Irwin, 2004;Salazar & Baxter, 2015) • Porous boundaries of problem: Complex problems of survival are not isolated, but rather resonate with other such complex problems exerting pressure on each other. Changes in one affect another, therefore, entangling an interconnected to seek independesnt resolutions is difficult.…”
Section: Nature Of the Complex Problems Of Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Designing living systems is an interconnected interaction of continuously evolving and self-organizing interventions for long-term vision of sustainable future. (Irwin, 2004;Salazar & Baxter, 2015) • Porous boundaries of problem: Complex problems of survival are not isolated, but rather resonate with other such complex problems exerting pressure on each other. Changes in one affect another, therefore, entangling an interconnected to seek independesnt resolutions is difficult.…”
Section: Nature Of the Complex Problems Of Survivalmentioning
confidence: 99%
“…Introspection has revealed that unintended consequences of designed artifacts have induced inequitable contestations, and unsustainable practices in our social and environmental ecology. (Baek, Meroni, & Manzini, 2015;Fallan, 2014;Margolin, 1996;Papanek, 1972;Salazar & Baxter, 2015) But, we are also aware of the potential and central role played by responsibly designed artifacts to achieve a sustainable (Escobar & Jacoby, 2009;Fallan, 2014;Fuad-luke, 2007;Fuad-Luke, 2009;Manzini, 2016;Margolin, 1996) future. This implies possible opportunities for framing processes for our own collective survival, and the central role played by human and nonhuman actors in the process of resolution.…”
Section: Nature Of the Complex Problems Of Survivalmentioning
confidence: 99%
“…Although the purpose of this article is not to explore the foundations of this new paradigm, especially as others such as Capra (1996Capra ( , 2004 and Wilber (2000a, b) have already done so, it is necessary to emphasize that ecological urbanism must be understood within this framework. Thus, there are four fundamental and cross-cutting aspects to these emergent lines of thinking, which are important for ecological urbanism (Salazar & Baxter 2015): 1) a criticism of the modern paradigm regarding its assumption of a transcendental reality that exists independently of human relations and experience; 2) that human perception is an embodied phenomenon, the knowledge point of departure and ways of inhabiting the world; 3) that the world where we live, or the phenomenological Being-in-the-World, is a dynamic relational process that is constantly changing, in which the being and the world are an inseparable phenomenon; and 4) that the wellbeing of humans and the rest of the biosphere are complementary (Primack et al, 2001).…”
Section: Introductionmentioning
confidence: 99%